Model Pengelolaan Tempat Pengolahan Sampah Reduce Reuse Recycle (TPS 3R) - Setiyawan, Ended; Nurwati, Ucu (Koaliansi : Cooperative Journal, 2023)
It was found that waste management at TPS 3R in Genteng Village and Mekarsari Village, Sukasari District, Sumedang Regency, was found to be not working, that: the Cator garbage collector was inadequate because of the hillside area. The competence of TPS 3R managers needs to be improved by training in skills and knowledge of waste processing management. As well as the need to increase socialization and outreach to the community regarding the waste management program collectively and massively, so that community participation in the TPS 3R program is high. The purpose of this research is to establish a TPS 3R model that is suitable for the Genteng Village and Mekarsari Village areas. With qualitative research methods in the form of observation, interviews, as well as documentation and literature studies. The results of the study show that the 3R TPS Management Model in Genteng Village and Mekarsari Village is a stage that must be initiated: 1. Massive and periodic outreach and counseling to community members, so that community participation in the use of 3R TPS is high. 2. Establish a waste bank and business entity to buy & sell economic waste from community members. 3. It is mandatory to become a TPS 3R beneficiary member for places of business and educational institutions, both public schools and Islamic boarding schools. 4. Utilizing social media to coordinate beneficiary members. 5. TPS conducts activities 2 times a week including collection, sorting and burning of waste. As well as making organic fertilizer as a TPS 3R product.